PERAN MOTIVASI INTRINSIK DALAM PENGARUH KOMITMEN AFEKTIF DAN KOMPETENSI TERHADAP KINERJA KARYAWAN DISABILITAS - Ignatius Soni Kurniawan Soni (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Serang Raya, 2021)
This study aims to determine the effect of affective commitment and competence on employee performance with intrinsic motivation as a mediating variable. The research was conducted on 82 employees with disabilities who work at various companies in Indonesia that use the media Kerjaabilitas.com. The data were collected through a survey with a questionnaire that was distributed online. The findings show that there is a mediating role of intrinsic motivation on the effect of affective commitment on employee performance. It was also found that competence has a direct effect on performance without being mediated by intrinsic motivation.